2008
DOI: 10.1370/afm.889
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Automated Telephone Self-Management Support With Nurse Care Management Among Patients With Diabetes

Abstract: PURPOSE This study evaluated the cost-effectiveness of an automated telephone self-management support with nurse care management (ATSM) intervention for patients with type 2 diabetes, which was tested among patients receiving primary care in publicly funded (safety net) clinics, focusing on non-English speakers. METHODSWe performed cost analyses in the context of a randomized trial among primary care patients comparing the effects of ATSM (n = 112) and usual care (n = 114) on diabetes-related outcomes in 4 San… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
93
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(97 citation statements)
references
References 35 publications
2
93
0
2
Order By: Relevance
“…Mobile health (m-health) services seek to increase access to between-visit support by augmenting clinician contact with automated services delivered via smart phones, 8 short message service (text messaging), [9][10][11][12] and automated calls. [13][14][15][16][17] Automated telephone management and behavior-change calls can improve selfcare and health outcomes among NCD patients and may be more cost-effective than in-person visits or calls with ''live'' clinicians. [14][15][16][17] However, rigorous studies of m-health services in LMICs are rare.…”
Section: Telehealth and Mobile Health In Chronic Disease Managementmentioning
confidence: 99%
“…Mobile health (m-health) services seek to increase access to between-visit support by augmenting clinician contact with automated services delivered via smart phones, 8 short message service (text messaging), [9][10][11][12] and automated calls. [13][14][15][16][17] Automated telephone management and behavior-change calls can improve selfcare and health outcomes among NCD patients and may be more cost-effective than in-person visits or calls with ''live'' clinicians. [14][15][16][17] However, rigorous studies of m-health services in LMICs are rare.…”
Section: Telehealth and Mobile Health In Chronic Disease Managementmentioning
confidence: 99%
“…Handley et al used the cost to achieve a 10% increase in the proportion of participants achieving recommended moderate or vigorous physical activity levels in a study involving adults with type 2 diabetes. 22 The annual cost to increase activity by 10% for the automated telephone surveillance and nurse care management was estimated to be €551 per participant. In contrast, two studies by Elley et al 11,27 used a threshold of 5 x 30 minutes of activity per week and found the cost per person to be €957 when predominantly doctor delivered, 11 and €331 when nurse delivered.…”
Section: Qaly = Quality-adjusted Life-yearmentioning
confidence: 99%
“…With different infrastructures, funding models, and cost structures, it is also difficult to make comparisons between different countries. Furthermore, some studies included funder costs only, 17,[21][22][23][24][25][26] while others presented societal perspectives that also included costs to the participant. 11,[18][19][20]27 Consequently, there was a wide variation in costs per QALY gained between the studies.…”
Section: Qaly = Quality-adjusted Life-yearmentioning
confidence: 99%
“…6 Mobile health (m-health) tools are part of a comprehensive plan to improve chronic illness care in LMICs. [7][8][9] Trials indicate that interactive voice response (IVR)-based interventions effectively address diabetes risk factors such as poor diet and sedentary behavior, [10][11][12] and IVR-supported nurse follow-up can improve glycemic control and self-care after diabetes is diagnosed. [12][13][14] In Honduras, weekly IVR self-management support calls were associated with improved diabetes self-management and A1c levels, 15 and in Honduras and Mexico, a similar IVR-based intervention resulted in better blood pressure control and improved self-care among hypertensive patients.…”
Section: Introductionmentioning
confidence: 99%